Epidemiological Study to Assess the Prevalence of Lung Cancer in patients with smoking-associated atherosclerotic cardiovascular diseases: PREVALUNG study protocol - Gilles Chatellier; Laurence Zitvogel; Benjamin Besse; Caroline Caramella; Marine Fidelle; David Boulate; Justin Issard; Olivier Planché; Pauline Pradère; Daniel Garelik; Océane Hache; Lilia Lamrani; et al. (BMJ Open)
Introduction Eligibility criteria definition for a lung cancer screening (LCS) is an unmet need. We hypothesised that patients with a history of atheromatous cardiovascular disease (ACVD) associated with tobacco consumption are at risk of lung cancer (LC). The main objective is to assess LC prevalence among patients with ACVD and history of tobacco consumption by using low-dose chest CT scan. Secondary objectives include the evaluation LCS in this population and the constitution of a biological biobank to stratify risk of LC.Methods and analysis We are performing a monocentric ‘single-centre’ prospective study among patients followed up in adult cardiovascular programmes of vascular surgery, cardiology and cardiac surgery recruited from 18 November 2019 to 18 May 2021. The inclusion criteria are (1) age 45–75 years old, (2) history of ACVD and (3) history of daily tobacco consumption for 10 years prior to onset of ACVD. Exclusion criteria are symptoms of LC, existing follow-up for pulmonary nodule, fibrosis, pulmonary hypertension, resting dyspnoea and active pulmonary infectious disease. We targeted the inclusion of 500 patients. After inclusion (V0), patients are scheduled for a low-dose chest CT and blood and faeces harvesting within 7 months (V1). Each patient is scheduled for a follow-up by telephonic visits at month 3 (V2), month 6 (V3) and month 12 (V4) after V1. Each patient is followed up until 1 year after V1 (14 February 2023). We measure LC prevalence and quantify the National Lung Screening Trial and Dutch-Belgian Randomized Lung Cancer Screening Trial (NELSON) trial eligibility criteria, radiation, positive screening, false positivity, rate of localised LC diagnosis, quality of life with the Short Form 12 (SF-12) and anxiety with the Spielberger State-Trait Anxiety Inventory A and B (STAI-YA and STAI-YB, respectively), smoking cessation and onset of cardiovascular and oncological events within 1 year of follow-up. A case–control study nested in the cohort is performed to identify clinical or biological candidate biomarkers of LC.Ethics and dissemination The study was approved according the French Jardé law; the study is referenced at the French ‘Agence Nationale de Sécurité du Médicament et des Produits de Santé’ (reference ID RCB: 2019-A00262-55) and registered on clinicaltrial.gov. The results of the study will be presented after the closure of the follow-up scheduled on 14 February 2023 and disseminated through peer-reviewed journals and national and international conferences.Trial registration number NCT03976804.